2012
DOI: 10.1155/2012/508294
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Substrate Mechanics on Contractility of Cardiomyocytes Generated from Human Pluripotent Stem Cells

Abstract: Human pluripotent stem cell (hPSC-) derived cardiomyocytes have potential applications in drug discovery, toxicity testing, developmental studies, and regenerative medicine. Before these cells can be reliably utilized, characterization of their functionality is required to establish their similarity to native cardiomyocytes. We tracked fluorescent beads embedded in 4.4–99.7 kPa polyacrylamide hydrogels beneath contracting neonatal rat cardiomyocytes and cardiomyocytes generated from hPSCs via growth-factor-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
136
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(150 citation statements)
references
References 40 publications
11
136
2
1
Order By: Relevance
“…2C. The failure of the CE model on soft gels is expected from cultured CM experiments (7,8,22). Remarkably, we find agreement between the SE model with cell-on-gel measurements, demonstrating that we can deduce this single CM behavior as a function of E quantitatively from collective behavior in tissue.…”
Section: Se Model Is Consistent With Cell-on-gel Measurements With Nosupporting
confidence: 65%
See 1 more Smart Citation
“…2C. The failure of the CE model on soft gels is expected from cultured CM experiments (7,8,22). Remarkably, we find agreement between the SE model with cell-on-gel measurements, demonstrating that we can deduce this single CM behavior as a function of E quantitatively from collective behavior in tissue.…”
Section: Se Model Is Consistent With Cell-on-gel Measurements With Nosupporting
confidence: 65%
“…1A, Inset). This behavior is observed for embryonic and neonatal CMs cultured on hydrogels (5,7,8,22) and has been studied theoretically (23).…”
Section: Physical Model Of Cardiac Mechanical Signalingmentioning
confidence: 81%
“…Previous studies found that 10-kPa substrates yield useful cultures of immature primary neonatal murine CMs with physiological shape (21,23). Increasing substrate stiffness without controlling cell shape increases the force output of neonatal murine CMs (25) and unpatterned hPSC-CMs (24). We found that variations in stiffness affect the mechanical output of engineered hPSC-CMs by changing myofibril function.…”
Section: Discussionmentioning
confidence: 53%
“…Along with cell shape, substrate stiffness affects the cytoskeleton (23) and mechanical phenotypes of cells (24,25) and may regulate the mechanical output of engineered hPSC-CMs. Generally, tension along the cell membrane increases with the aspect ratio of adherent cells (26).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, both the morphology and beating of embryonic heart muscle cells or cardiomyocytes have been observed to depend sensitively on the rigidity of the substrate on which they are cultured [4][5][6][7][8] .…”
mentioning
confidence: 99%